The factors that affect the profitability performance of Islamic banking institutions in Malaysia / Sri Farah Ain Shaib and Syazana Abd Aziz - Shaib, Sri Farah Ain; Abd Aziz, Syazana (2014)
This study is able to determine the factors that affect the profitability performance in Islamic Banking in Malaysia that cover thirteen years period starting in year 2000 until 2013. The data has been analyzed to determine the factors that affect profitability of Islamic banking institutions. Meanwhile, to identify the factors of its profitability , the Least Square Method has been used. All the data had been obtained from secondary sources through published journal , books, working papers , annual bank report and etc. Malaysia has been proved to be the at the forefront of Islamic banking and finance in the world wide. There are gaining popularity among non-Muslim across the globe due to its wider product and services. Hence, this study is carried out to identify the factors that affect the profitability performance of Islamic Banking Institutions in Malaysia. Based on the findings, financing , capital and fuel price are significantly determinants impact on Islamic banks’ profitability. Financing is positively related while capital and fuel price are negatively to Islamic banks’ profitability. Meanwhile the other determinants such as cost management, cyclical output (GDP growth rate and GDP deflator (the expectation of inflation) are do not significantly to Islamic banks’ profitability in Malaysia. As a conclusion , it is hoped this study can give better knowledge and understanding to Islamic Banking institution and new factors would identified that can be taken to determinants of influences in profitability Islamic Banking institutions in Malaysia.